The classification of naturally graded Zinbiel algebras with characteristic sequence equal to $(n - p,\, p) $ - Adashev, J. K.; Ladra, M.; Omirov, B. A. (Ukrains’kyi Matematychnyi Zhurnal, 2019)
UDC 512.5 This work is a continuation of the description of some classes of nilpotent Zinbiel algebras. We focus on the study of Zinbiel algebras with restrictions imposed on gradation and characteristic sequence. Namely, we obtain the classification of naturally graded Zinbiel algebras with characteristic sequence equal to $ (n-p, p)$.